THE CHALLENGE OF ENVIRONMENTAL RESEARCH - Seiffert, Nelson Frederico (Science & Technology Journals, 1998)
The purpose of this paper is to discuss available environmental resource management instruments, sustainable rural development, and research contributions to minimize the environmental impact of agriculture on the ecossistem, under the AGENDA 21 principles. Environmental research potentials are evaluated, and advances and obstacles of legal, institutional, political, economic and educational nature are characterized. Restrictions that delay institutional advances in the implementation of environmentaly sustainable agriculture ecossistems are stressed. The intention of the discussion is to stimulate planners, researchers and technicians, toward a clearer perception of the obstacles and strategies that could encourage Embrapa to assume the challenge of environmental research.